Stuttering Due To Ischemic Stroke - Huseyin Alparslan Sahin; Yakup Krespi; Ahmet Yilmaz; Oguzhan Coban (Behavioural Neurology)
Acquired stuttering is a disorder of the fluency of speech. The mechanism underlying stuttering is unknown. It may occur after bilateral and unilateral cortical or subcortical brain damage. We report two cases who had stuttering resulting from left parietal infarction.